Estimate the effect of Male frankincense (Boswellia Carterii ) extracts' on the Bacteriological and chemical quality of chicken meat - Shaimaa Abbas Sabeeh (Zien Journals, 2023)
This study's objective is to determine the influence of applying the ethanolic alcoholic extract of the male frankincense (Boswellia carterii plant) on extending the shelf life of raw chicken. Meat stored at 4 °C for 9 days A total of 100 g of broiler chicken meat mixed with concentrations of 100, 200, and 400 mg/ml of Boswellia Carterii, respectively, and 0 (control sample) was stored separately for 0 days to determine the microbiological and chemical quality of the meat. This involved performing various plate count indicators, including total bacterial count (TBC), total coliform count (TCC), TBARS levels, and pH. In all treated samples compared to the control, there were significant differences in concentration (P <0.05) and storage period P><0.05 on the third, fifth, and ninth days of refrigeration). The meat was preserved longer when mixed with frankincense extract, according to the results. The results showed better results when using the alcoholic extract of frankincense at a concentration of 400 mg/ml for 9 days at a temperature of 4 °C, where the number of microorganisms decreased significantly more than at the other concentrations used, 100 and 200 mg/ml, respectively), all of which conformed to the Iraqi standard in terms of human consumption. >
Keywords: Boswellia Carterii; extract; Bacteriological analysis; chicken meat